Social capital and trade credit - Hasan, Mostafa; Habib, A. (Elsevier BV, 2018)
© 2018 Elsevier Inc. We investigate the relation between social capital and firms’ use of trade credit in the USA. We also estimate the extent to which social capital is both directly and indirectly related to firms’ use of trade credit. Using a large sample of US data, we find robust evidence that firms headquartered in high social capital counties use less trade credit: a finding that is both statistically and economically significant. Our analysis also reveals that social capital, both directly and indirectly (through the financial constraints channel), influences firms’ use of trade credit. An additional analysis reveals that the county-level social norms provide the mechanism through which social capital influences firm-level trade credit. Our results are robust to alternative measures of social capital and trade credit, and are not driven by omitted variable bias or endogeneity issues. Overall, our results show that county-level social capital influences organizational outcomes.